Book Review: ISLAM AND BIOMEDICINE by Afifi al-Akiti & Aasim I. Padela (Editors) - Hanish, Irwan (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2023)
Afifi al-Akiti & Aasim I. Padela, eds., Islam and Biomedicine, Cham: Springer International Publishing, 2022. 326 pp. ISBN 978-3-030-53800-2. The book, Islam and Biomedicine, initiates conversations at the junction between the rich Islamic intellectual tradition and the diverse disciplines of Biomedicine. The project has brought together scholars from diverse backgrounds to engage with a critical question: How do biomedical advancements might inform and work with Islamic theological and philosophical traditions?